Shadowed by Giants: Desert Plants Versus Rainforest Plants as Targets for Novel Antibacterial Drug Discovery - Wright, Mitchell Henry; Cock, Ian Edwin (Pharmacognosy Communications)
The escalating global crisis of bacterial resistance to antibiotics poses a threat to public health. Urgent measures are required to identify novel antibacterial treatments. Multidrug-resistant bacterial strains limit the effective therapeutic options available, raising concerns about a post-antibiotic era and a reduced ability to treat infections that were previously not classified as serious. Simultaneously, the threat of emerging infectious diseases, including zoonotic pathogens, underscores the need to develop effective antibiotics against these pathogens. Innovative approaches to antibiotic development, such as novel chemical scaffolds, combination therapies, antimicrobial peptides, and phage therapy, show promise but require the discovery of new antibacterial compounds. Desert and rainforest ecosystems, despite being disparate in climate and biodiversity, offer unique prospects for developing antibacterial compounds. Deserts, which are characterized by extreme aridity and temperature fluctuations, harbor plants and micro-organisms with specialized antibacterial defences honed through evolution. Conversely, rainforests, with their biodiversity and high humidity, are promising for the development of potential antibacterial compounds. To date, much natural product research aimed at discovery of new antibiotic compounds has focussed on rainforest plants due to the biodiversity of these ecosystems, and because plants develop chemical defences against microbes that are prevalent in those environments. In comparison, the search for new antimicrobial compounds from desert plants has been overshadowed, despite some noteworthy antibacterial activities in arid environment plants. This commentary discusses the comparative potential of desert and rainforest ecosystems as reservoirs of novel antibacterial agents and emphasises the importance of screening plants in both environments.
Keywords: Antibiotic resistance; Biodiversity; Traditional medicine; Bioprospecting; Ethnobotany; Natural medicine